A pedagogia do jogo no contexto escolar - Castro, Lígia Estronioli de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
As the ludic taking the second place at school environment, on account of logical and rational activities and the excessive charge of a professional achievement of children by society and, also, the own family, the school doesn't become a pleasant ambient of frequenting. This study wants to understand, in a better way, the utilization of ludic activities as a pedagogic support into the learning and the development of the cognitive, emotional and creative potentiality of children in different education system (public and private) of Ibitinga-SP. It also investigates the docent attitude and practice during the ludic activities and its repercussion in the students' performances when introduced. The bibliographic researches present that the utilization of games, as a pedagogic resource, contributes to the learning process and to the human development of the students from the first cycle of the Elementary School. The School has to rescue the desire of learning, which is playing, the most natural way. The research's target audience are teachers from the Ciclo I of the elementary school and the focus is the utilization of the ludic into the different areas of teaching, considering the context that the schools are embedded. The reality observation, which enables a straight contact with the researcher and the study object, helped out with the issue comprehension. It was possible to identify that the utilization of ludic activities as a pedagogic strategy does not happen just because of knowledge absent, but also because of the submission to many goals imposed by the education system and/or by the didactic materials used, which don't have any worry to valorize the period of develop that the students are living, filtering out some characteristics from the phase that contributed to the learning. The responsibility to create a new signification to their social function is from the education system and the school that works with it. To the...

Com a secundarização do lúdico no ambiente escolar, por conta de tarefas mais racionais e a cobrança excessiva de realização profissional da criança por parte da sociedade e da própria família, a escola não se torna um ambiente prazeroso de se frequentar. O estudo presente busca compreender melhor a utilização de atividades lúdicas como suporte pedagógico na aprendizagem e para o desenvolvimento das potencialidades cognitiva, afetiva e criativa da criança nas diferentes redes de ensino (pública e particular) da cidade de Ibitinga-SP. Também investiga a postura e a prática docente nas atividades lúdicas e a sua repercussão no desempenho dos alunos quando introduzidas. As pesquisas bibliográficas apresentam que a utilização de jogos, como recurso pedagógico contribuem para o processo de aprendizagem e desenvolvimento humano dos alunos do primeiro ciclo do ensino fundamental. A escola deve resgatar a vontade de aprender da forma mais natural possível, que é brincando. O público alvo da pesquisa são professores do ciclo I do ensino fundamental e o foco é a utilização do lúdico nas diferentes áreas deste ensino, considerando o contexto em que as escolas se inserem. A observação da realidade, a qual possibilitou o contato direto da pesquisadora com o objeto de estudo, auxiliou na compreensão da problemática. Foi possível identificar que a utilização de atividades lúdicas como estratégia pedagógica, não acontece só por falta de conhecimento, mas também pela submissão a diversas metas impostas pelo sistema educacional e ou pelo material didático utilizado, que não tem preocupação de valorizar o período de desenvolvimento que os alunos estão vivendo, ignorando características da fase que contribuiriam para o progresso da aprendizagem. Cabe então, em primeiro lugar, ao próprio sistema educacional e a escola resignificarem sua função social e aos professores, refletirem sobre a atuação profissional...
Keywords: Disturbios da aprendizagem nas crianças; Jogos educativos; Aprendizagem; Dificuldades no Ensino; Disturbios da aprendizagem; Learning disabled children